Breastfeeding and Bottle Feeding Practices: A Phenomenon towards Infant Feeding Practices in Semarang - Margawati, Ani (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2007)
Background: Breastfeeding is regarded as good practice today. Women are encouraged to breastfeed and to continue breastfeeding for at least four to six months. In Indonesia, a campaign for exclusive breastfeeding was introduced more than 20 years ago. However, the Indonesian Demographic and Health Survey (IDHS) 2002 show that only 55.1 percent of babies were breastfed exclusively until four months old.Method: The purpose of this paper is to examine breastfeeding and bottle feeding practices among women in Semarang based on socio-cultural factors. The respondents for the study were, respectively, pregnant and breastfeeding women who living in Lintang village in Semarang. A qualitative data collection method was used in this research. The methods employed for qualitative data collection included focus group discussions, informal and in-depth interviews and participant observation.Results: This study found that the mothers in Lintang village stated that breastfeeding is healthy, cheap and practical. They perceived breastfeeding to be a natural process, part of a women’s duty and good parenting, which promotes a good relationship between mother andbaby. However, this study found that they lack a complete of understanding of the processes and nutritional issues involved in breastfeeding. This researchalso found that inconsistency in government policies to support the breast-feeding programmes, such as the poor implementation of the ‘baby friendly hospital’ with ‘rooming-in programmes’ and also the length of maternity leave for working women, have led to an increase in bottle-feeding practices in IndonesiaKeywords: Breastfeeding practice; Socio-cultural aspects; Bottle feeding practice